AN EXPLORATION OF HOW NICHE CLOTHING BRANDS VALUE RACIAL DIVERSITY AND THE EFFECTS ON WOMEN OF COLOUR: A QUALITATIVE STUDY - Beaumont, Micaela (The IIE, 2019)
This study aims to understand the effects racial diversity has on women of colour living in the City of Cape Town, Western Cape. Likewise, exploring how niche clothing brands currently value racial diversity. Intersectional feminism was the theoretical lens for this study. The researcher made use of qualitative research methods, with triangulation as the design; online questionnaires were used to gain qualitative and quantitative data. These questionnaires explored the current perceptions of racial diversity, and the value brands and consumers have over the matter. In conducting the research, the researcher found that clothing brands often overlook racial diversity because they often do not have the means to be diverse. Brands can identify the importance of racial diversity but cannot create a link between race and colour (complexion). Regarding consumers, many expressed their desire to support racially diverse brands, while others did not carefully consider the matter as it may be unimportant or irrelevant. Both samples were able to understand the strength brands hold in the portrayal of women of colour. Although the research was done using a small sample, it highlights the importance and relevance of racial diversity. Racial diversity should be integrated into the brands’ business models to create authentic connections with the South African market.
Keywords: Clothing brands; Racial diversity; Feminism; Intersectional feminism; Fashion industry; Consumer behaviour